Scaling of the Parameters for Cost Balancing in Self-Organized Task Switching. Issue 1 (18th January 2021) - Monno, Irina; Spitzer, Markus; Miller, Jeff; Dignath, David; Kiesel, Andrea
Previous studies on voluntary task switching using the self-organized task switching paradigm suggest that task performance and task selection in multitasking are related. When deciding between two tasks, the stimulus associated with a task repetition occurred with a stimulus onset asynchrony ( SOA ) that continuously increased with the number of repetitions, while the stimulus associated with a task switch was immediately available. Thus, the waiting time for the repetition stimulus increased with number of consecutive task repetitions. Two main results were shown: first, switch costs and voluntary switch rates correlated negatively – the smaller the switch costs, the larger the switch rates. Second, participants switched tasks when switch costs and waiting time for the repetition stimulus were similar. In the present study, we varied the SOA that increased with number of task repetitions ( SOA increment ) and also varied the size of the switch costs by varying the intertrial interval. We examined which combination of SOA increment and switch costs maximizes participants' attempts to balance waiting time and switch costs in self-organized task switching. We found that small SOA increments allow for fine-grained adaptation and that participants can best balance their switch costs and waiting times in settings with medium switch costs and small SOA increments. In addition, correlational analyses indicate relations between individual switch costs and individual switch rates across participants.